Fostering Social Cohesion: The Impact of Citizen Participation in Pakistan - Muhammad Nadir; Saima Bashir (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
Social cohesion is a critical element in ensuring political stability, inclusive development, and sustainable governance in diverse societies. This study examines the relationship between civic participation and social cohesion in Pakistan, with particular emphasis on the role of participatory governance, community engagement, and policy frameworks in promoting inclusive development. Using a qualitative analytical approach, the study draws on academic literature, government policies, and civil society initiatives to evaluate how citizen participation strengthens social bonds, collective identity, and trust among diverse social groups. The findings suggest that civic engagement initiatives—including youth participation programs, community development projects, and interfaith dialogue platforms—play an important role in bridging ethnic, religious, and socio-economic divisions. However, challenges such as economic inequality, political instability, and limited policy implementation continue to hinder the effectiveness of these initiatives. Drawing on insights from Islamic economics, the study highlights the potential of Islamic social finance instruments, such as zakat, waqf, and sadaqah, to support community development and reduce socio-economic disparities. Furthermore, the principle of shura (consultative governance) provides a normative framework for strengthening participatory decision-making processes. The study concludes that combining participatory governance with Islamic economic principles can provide a culturally grounded approach to enhancing social cohesion and inclusive development in Pakistan.